ASSESSMENT OF FLORAL STAGE-SPECIFIC FROST INJURY UNDER CONTROLLED CONDITIONS AND EVALUATION OF MITIGATION SYSTEMS IN A'FUJI’ APPLE ORCHARD - Je-Chang Lee; Jae-Yun Heo (Journal of Animal and Plant Sciences, 2026)
In recent years, the apple cultivar ‘Fuji’ has frequently suffered frost injury during the flowering period in Korea due to climate change, posing serious challenges to yield stability. This study evaluated the frost tolerance of ‘Fuji’ flower organs across developmental stages and assessed the field applicability of wind machines and sprinklers as frost protection measures. Controlled freezing tests using floral samples from M.9-grafted trees demonstrated that frost sensitivity increased as development progressed, with injury evident from –4 °C at the tight cluster stage and complete necrosis observed at –2 °C during full bloom. To assess practical effectiveness, an on-farm trial was conducted during a natural frost event in 2021. The wind machine increased orchard air temperature by up to 2.2 °C but had minimal effect on humidity, whereas the sprinkler system moderately raised temperature and markedly elevated relative humidity by more than 10%. These modifications reduced floral injury rates to 17.8% and 19.5%, compared with 28.2% in the untreated control. These findings provide quantitative evidence that both technologies can substantially mitigate frost injury. By demonstrating significant reductions in floral damage under natural conditions, this study underscores their potential to enhance yield stability and strengthen the climate resilience of apple production in frost-prone regions.
Keywords: Climate change; Field; Flower; Freezing; Malus x domestica